RENCANA PEMULANGAN DAN INTEGRASI EKS PENDERITA GANGGUAN MENTAL DENGAN MASYARAKAT: MASALAH DAN SOLUSI - Husmiati, Husmiati (Sosio Informa : Kajian Permasalahan Sosial dan Usaha Kesejahteraan Sosial, 2016)
In general, ordinary people still consider that the people, who used to suffer from mental disorder and who was declared to have been recovered, have a negative label. Such labeling can affect the people’s treatment on them as well as on their families. The impact of this problem will be more serious for them, such as: neglect, discrimination, oppression, social isolation and the omission on them to be homeless. This paper tried to analyze the issue of how the efforts of government and their family to plan the integration of the former mental disorder clients into their family and community. In addition, to analyze the issue of how the public accept the former mental disorder clients. The solution offered is the need of the efforts of accurate discharge and integration planning of the former mental disorder clients and the involvement of their family members, peers, neighbors and the community in maintaining their mental health status and the quality of their life. In addition, the government and the private sectors can play an important role to help the former mental disorder clients reintegrate into their families and communities. Keywords: the former mental disorder clients, discharge and integration planning.